Comparative Study of Android Smartphone-Based Antivirus Performance Using the TAM Method - Franco Turangan, Diah Ayu Utari, Krina Mawuntu (International Journal of Information Technology and Education, 2021)
Android is a mobile phone that has many advantages. Android has many interesting features and applications. Because the need for Android smartphones continues to grow rapidly at the same time technology is also increasingly sophisticated. This also has a weakness, namely by the presence of people who are not responsible for damaging the Android OS, where they will spread malware, spyware, trojans, and other viruses. To damage and steal data from the victim's android smartphone. The purpose of this study is to know the performance of smartphones when using antivirus. The method used in this research is the TAM (Technology Acceptance Model) method. TAM is one of the models built to analyze and understand the factors that influence the acceptance of the use of computer technology. The results of this study indicate that the appearance of the Avast antivirus and Clean Master has an attractive design, easy to operate, and the features of Avast are easy to understand. While the use of Avast antivirus and Clean Master can save time in operation, meet needs, and is efficient and effective, and its convenience can make it easier for users to use this antivirus more flexible